Volumetric changes in pharyngeal structures following head and neck cancer chemoradiation therapy. (1st July 2019) - Hinther, Ashley; Samson, Nina; Lau, Harold; Quon, Harvey; Banerjee, Robyn; Lysack, John T.; Grendarova, Petra; Matthews, T. Wayne; Randall, Derrick R.
Abstract : Objectives/Hypothesis: To determine the volumetric changes in pharyngeal structures in patients with head and neck squamous cell carcinoma (HNSCC) treated with curative chemoradiation therapy (CRT). Patients treated with CRT for esophageal carcinoma (EC), where pharyngeal structures were not part of the radiation treatment fields, were controlled for dysphagia‐associated weight loss. We hypothesize that tissue volume alteration is a contributing factor of post‐CRT dysphagia. Study Design: Case series. Methods: This study measured pre‐ and 1‐year posttreatment volumes of the base of tongue (BOT), parapharyngeal spaces, posterior pharyngeal constrictors (PCs), and retropharyngeal space (RPS) in patients undergoing CRT for HNSCC or EC treated January 1, 2012 to December 31, 2015. All HNSCC patients were treated to doses of 66 to 70 Gy in 30 to 33 fractions using intensity‐modulated radiotherapy techniques. Results: Our cohort included 49 HNSCC and 11 EC patients. Within the HNSCC cohort, the PCs volume increased 1.55 cm 3 (95% confidence interval [CI]: 0.77 to 2.34 cm 3, P = .0002), RPS increased 1.22 cm 3 (95% CI: 0.67 to 1.77 cm 3, P < .0001), and BOT decreased 2.29 cm 3 (95% CI: −0.20 to 4.79 cm 3, P = .070). The EC cohort showed no significant volumetric changes for any anatomic space, with combined PCs and RPS volume changes statistically less than the HNSCC cohort ( P = .031). There was no difference in mean body mass index reduction between groups ( P = .10). Conclusions: Volumetric changes following CRT may play a role in posttreatment dysphagia. Our findings support loss of physiologic function from posterior pharynx tissue thickening combined with reduced pharyngeal constriction capacity, and BOT atrophy secondary to radiation effects contribute to dysphagia. Level of Evidence: 4 Laryngoscope, 130:597–602, 2020